Toward On‐and‐Off Magnetism: Reversible Electrochemistry to Control Magnetic Phase Transitions in Spinel Ferrites. (7th September 2016) - Dasgupta, Subho; Das, Bijoy; Li, Qiang; Wang, Di; Baby, Tessy T.; Indris, Sylvio; Knapp, Michael; Ehrenberg, Helmut; Fink, Karin; Kruk, Robert; Hahn, Horst
Abstract : The magnetoelectric effect, i.e., electric‐field control of magnetism in artificial heterostructures is usually limited to surface/interface atoms of the magnetic materials. In order to attain electrical control of magnetism in bulk ferromagnets, this study proposes to extend the definition of magnetoelectric phenomena to include reversible, chemistry‐controlled magnetization switching. A large and reversible change in the room temperature magnetization in strong ferromagnets is reported, with electrochemistry‐driven Li‐ion exchange; carefully chosen spinel ferrites demonstrate a reversible magnetization variation up to 50% for CuFe2 O4 and 70% for ZnFe2 O4 . In case of CuFe2 O4, the magnetization variation is predominantly associated with the preferential reduction of Cu 2+ to Cu + ions, and, hence, abides a nearly one‐to‐one relationship with the amount of injected Li‐ions. In addition, the reduction of Cu 2+ also annihilates the Fe 3+ OCu 2+ magnetic interaction, resulting in a marked decrease in the Neél temperature of CuFe2 O4 . In contrast, the electrical tuning of superexchange interactions is found to play the decisive role in ZnFe2 O4, where the simple electrochemical reduction model of magnetic cations can only explain a nominal fraction of the total magnetization variation, and indeed an electrochemically controlled reversible change in transition temperature is found necessary to account for the large magnetization variation observed. Abstract : A judicious selection of magnetic systems results in an electrochemically driven, fully reversible, and near complete switching of room temperature magnetization in strong ferromagnets. Apart from the Li‐intercalation‐induced controlled reduction/oxidation of the magnetic cations, a reversible tuning of the magnetic transition temperatures is found to be responsible for the large magneto‐ionic effect observed.